TerriStories. Literary Tools for Capturing Atmosphere in Architectural Pedagogy - Klaske Havik (Ambiances)
By recognizing the potential of literary language in the description of architectural atmospheres, this contribution aims to confront the shortcomings of conventional pedagogical approaches in architecture that often fail to provide an in-depth understanding of the experiential aspects of place. To contribute to the development of appropriate instruments of analysis and design to read and describe urban atmosphere, this article combines two main insights: first, that it is of crucial importance to investigate site-specific atmospheres to understand how people experience the urban territories they use or inhabit; and second, that it is through literary devices that atmospheres can be read and described. By bringing together these insights, this article aims to propose pedagogical exercises that help students of architecture to develop a better understanding of the experiential aspects of site-specificity. By adding to the conventional tools of architect and planners a set of tools inspired by literature, it hopes to offer students in architecture more appropriate tools to describe, respond to, and produce site-specific atmospheres. It will illustrate the potential of this approach by presenting an example of the use of literary methods in architectural education, in Tampere, Finland.